LANGUAGE PORTFOLIO FOR BUILDING LINGUISTIC COMPETENCE IN ESP SPEAKING IN STUDENTS' INDEPENDENT WORK - Andiy Kotlovskiy; Nataliya Mykytenko; Andriana Onufriv; Maryana Salamakha (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The study shows that language portfolio is an effective tool which is applied in students' independent work. We aimed to survey students' views on the usage of language portfolio; to define the types of students' autonomy with teacher's guidance that contribute to successful acquisition of lexical and grammatical competences within students' independent work; to give recommendations to teachers about using language portfolio for building lexical and grammatical competences in ESP speaking. Thus, a mixed research design was employed. The qualitative research design relied on collecting data about students' attitude to using language portfolio as a tool of building their lexical and grammatical competences in ESP speaking within their independent work. The quantitative research design was focused on interpreting the results and suggesting recommendations regarding students' independent work in ESP learning. The research was held at Ivan Franko National University of Lviv during December-February of 2019-2020 academic year. The total number of full-time second-year students who took part voluntarily was 250. Also, five ESP teachers participated in the survey. Within the context of the study, the questionnaire was designed to identify students' attitude towards learning aims, ways to achieve them, type of teacher's guidance, practicability of keys, instructions, range of suitable techniques. The findings show that the students prefer relative autonomy and half-autonomy with a firm and relatively firm teacher's guidance to follow while acquiring lexical and grammatical competences in ESP speaking. Most students admit that language portfolio is an effective tool which promotes significant progress in their lexical and grammatical competences in ESP speaking.